AB0250 The value of referral letter information in predicting inflammatory arthritis – factors important for effective triaging. (23rd January 2014) - Tay, S.H; Lee, T. L.; Low, B.; Lim, A.; Cheung, P.
Abstract : Background: The management of patients with inflammatory arthritis relies on the principle that patients are referred to and reviewed by rheumatologists as soon as possible. Success of this depends upon accurate and thorough information being provided in the letter of referral as well as the rheumatologist themselves, in the interpretation of this information. Important components of an informative referral letter to rheumatologists have not been evaluated in an Asian setting. Objectives: To identify factors from referral information predictive of patients with inflammatory arthritis requiring early review. Methods: 426 consecutive rheumatologist-triaged referrals from February to June 2012 were retrospectively reviewed to identify patients with confirmed inflammatory arthritis after rheumatologist review, correctly triaged initially for review within 2 weeks from referral date. Appropriate early review was defined as patients with rheumatologist-diagnosed inflammatory arthritis (excluding crystal arthritis) reviewed within 2 weeks from referral. Data on provisional and final diagnoses, time to review and appropriateness of early review were collected. Information from the referral letters including age, gender, morning stiffness, number of joints involved, pattern of joint involvement, laboratory results such as rheumatoid factor, erythrocyte sedimentation rate (ESR) and uric acid (if available), were analysed descriptively followed by univariate logistic regression adjusted for age and gender to identify predictors of inflammatory arthritis diagnosis in referral letters. Results: 76 patients with inflammatory arthritis were correctly triaged with 45% having rheumatoid arthritis, 9% psoriatic arthritis, 9% spondyloarthritis and 18% with undifferentiated inflammatory arthritis. 63% were females, with median age 53 years (Q1; Q3 38; 61) with referrers indicating presence of morning stiffness in 71% and symmetrical distribution of joint involvement in 74%. More than 5 joints were involved in 66%, with suspected metacarpophalangeal joint (MCPJ) in 45% or proximal interphalangeal joint (PIPJ) involvement in 60%. Of the referrals with laboratory results, ESR was raised with median 43.5 mm/hr (Q1; Q3 24.8; 77.5) and normal median uric acid of 313 mmol/L (Q1; Q3 250; 364). Univariate analysis revealed that involvement of > 5 joints (p=0.008), MCPJ (p=0.003), PIPJ (p=0.003), symmetrical distribution (p=0.005), positive rheumatoid factor (p=0.029) and elevated ESR (p=0.001) predicted inflammatory arthritis after adjustment of age and gender. Conclusions: Referral letters to rheumatologists for an opinion of inflammatory arthritis should contain the factors relevant to a diagnosis of inflammatory arthritis as identified. It is possible that letters that do not contain all available information lead to patients being inappropriately triaged and having a delayed diagnosis. A standardized referral template would help improve waiting times for patients with inflammatory arthritis. Disclosure of Interest: None Declared